Hydrothermal growth of highly oriented single crystalline Ta2O5 nanorod arrays and their conversion to Ta3N5 for efficient solar driven water splitting - Su, Zixue; Wang, Lei; Grigorescu, Sabina Georgiana; Lee, Kiyoung; Schmuki, Patrik (Chemical Communications, 2014)
We grow vertically aligned single crystalline Ta2O5 nanorod arrays that can be converted to Ta3N5 nanorod arrays by nitridation. Combined with cobalt phosphate (Co-Pi) as a co-catalyst, such Ta3N5 nanorod photoanodes can yield photocurrent densities of ∼3.6 mA cm-2 at 1.23 VRHE and ∼8.2 mA cm-2 at 1.59 VRHE under AM 1.5G (100 mW cm-2) irradiation.
EAM Import::2019-03-13

Self-organized cobalt fluoride nanochannel layers used as a pseudocapacitor material - Lee, Chong-Yong; Su, Zixue; Lee, Kiyoung; Tsuchiya, Hiroaki; Schmuki, Patrik (Chemical Communications, 2014)
Aligned CoF2 nanochannel layers have been formed by self-ordering electrochemical anodization. In voltammograms these layers provide multiple oxidation states, an almost ideal rectangular pseudocapacitive behavior, a high specific capacitance and good capacitance retention. These layers may thus be promising for supercapacitor applications.
EAM Import::2019-03-13